2021
DOI: 10.3389/fimmu.2021.790317
|View full text |Cite
|
Sign up to set email alerts
|

Siglec Signaling in the Tumor Microenvironment

Abstract: Sialic acid-binding immunoglobulin-like lectins (Siglecs) are a family of receptors that recognize sialoglycans – sialic acid containing glycans that are abundantly present on cell membranes. Siglecs are expressed on most immune cells and can modulate their activity and function. The majority of Siglecs contains immune inhibitory motifs comparable to the immune checkpoint receptor PD-1. In the tumor microenvironment (TME), signaling through the Siglec-sialoglycan axis appears to be enhanced through multiple me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 199 publications
(342 reference statements)
0
37
0
Order By: Relevance
“…Sialoglycans interact with Siglec-9 colocalized with the TCR-CD3 complex to inhibit TCR-mediated cell activation via recruitment of SHP-1 by ITIM phosphorylation to reduce ZAP 70 phosphorylation [ 57 ]. In addition, sialoglycans as alternative ligands of CD28 bind to CD80 on APCs, attenuating co-stimulatory signals of antigen-mediated activation of T cells [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sialoglycans interact with Siglec-9 colocalized with the TCR-CD3 complex to inhibit TCR-mediated cell activation via recruitment of SHP-1 by ITIM phosphorylation to reduce ZAP 70 phosphorylation [ 57 ]. In addition, sialoglycans as alternative ligands of CD28 bind to CD80 on APCs, attenuating co-stimulatory signals of antigen-mediated activation of T cells [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding our data about immune changes to corticosteroids, it is noteworthy the expression of sialic acid-binding immunoglobulin-type lectins (Siglecs) on monocyte cells. Targeting Siglecs has recently emerged as a promising therapeutic strategy in cancer [ 49 , 50 , 51 , 52 ]. In our study, we found that expression of both Siglec-3 (CD33) and Siglec-5 (CD170) increased after corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant glycosylation is a universal hallmark of cancer cells, commonly characterized by anomalous expression and glycosylation of mucins, abnormal branching of N-glycans, and increased expression of sialoglycans on proteins and lipids 98 , 99 . Sialic acid-binding immunoglobulin-like lectins (Siglecs) expressed on most immune cells are receptors for tumor-cell-derived sialoglycans, and the signaling through the sialoglycan-Siglec axis is similar to the PD-1/PD-L1 signaling, which stifles the anti-tumor immunity and brings about immunosuppressive TME 100 , 101 , 102 . Hitherto few targeted nanomedicines interfering with the sialoglycan-Siglec immune checkpoint have been brought up, it is a potential approach for enhancing cancer immunotherapy.…”
Section: Formation Mechanisms Of Immunosuppressive Tmementioning
confidence: 99%